TECHNOLOGY OF PRODUCTION OF METHANOL-BASED FUEL CELLS AND ITS EFFICIENCY - Suleymenova Manzura Polatovna; Odilova Nozima Akbar qizi; Omanov Behruzjon Shuhrat oglu (Western European Studies, 2025)
This article presents thoughts and considerations about what methanol is. How it is obtained, current technology and efficiency of obtaining methanol, and in which fields it is used. These articles discuss the advantages, disadvantages, and efficiency of methanol fuel cell technology.
Keywords: methanol; methyl alcohol; methanol fuel elements